Black holes and accretion in strong f(R) gravity - Pérez, Daniela (2012)
We discuss the characteristics of rotating black holes in modified theories of gravity. We present relativistic accretion disk models for matter falling into the black holes and elaborate about possible tests of gravity in the strong regime based on X-ray observations of systems like Cygnus X-1.